An Innovative Strategy in Learning English as A Foreign Language - rafiqa, Rafiqa; Yasim, Sukmawati; Paris, Nirma; Sabil, Marhaeni (Institut Agama Islam Negeri Parepare, 2024)
The present study aimed to delve into the students’ EFL vocabulary and response to the discovery learning strategy. A pre-experimental research design was applied in this study. The population of this study was first-year Sulawesi Barat University students who enrolled in vocabulary courses in the first semester, and the researchers used a random sampling technique to choose 42 students. This study found that the discovery learning strategy elevated the students’ English vocabulary. It was found that there are critical contrasts between the mean scores of the pre-test and post-test. The students’ pre-test score was 63.42, and the understudies' post-test score was 89.09, which is higher than the pre-test score. It demonstrated a critical improvement in students' accomplishment after carrying out revelation learning in instructing English vocabulary. Another result revealed that the students provided positive responses toward applying the discovery learning strategy in learning vocabulary, stated 53% of students agreed and 33% strongly agreed with the strategy, however 10% neutral, 3% disagreed and 1% strongly disagreed. Based on positive responses, the most of the students perceived that the discovery learning strategy benefits them in learning English.